Applying a decolonization paradigm to planning theory for inclusion and equity - Buttner, Dane; Nel, Verna; Mphambukeli, Thulisile Ncamsile (Frontiers in Sustainable Cities, 2025)
The Global North has dominated the planning theories for decades to resolve planning problems globally. These Northern theories were not feasible for most problems in the Global South, as the continued use of Northern theories maintains the inequalities of disjointed and divided cities caused by colonialism. However, as this approach is inappropriate and inadequate, planning theories require decolonization from the continued focus on the Global North in order to reflect the realities of the South. This paper contributes to the scholarship of decolonization in planning by investigating how planning academics and professionals in South Africa view the progress made in the decolonization of planning theories for inclusion and equity.